Formação de professores, inclusão e análise do comportamento: uma análise das publicações de trabalhos científicos no período de 2010 a 2019 - Gabiatti, Joselaine Aparecida (2020)
In this research, we analyzed the characteristics of Brazilian publications with the theme education x inclusion in the period 2010-2019. We analyzed 14 studies (13 articles and 1 book chapter) found from database research (BVS_PSI, Periódicos Capes), search engine (academic Google) and reference collections in behavior analysis ("About Behavior and Cognition" and "Behavior in Focus"), from categories and subcategories previously extracted from literature in the area, namely: objective; type of work; research design; materials and instruments used (for the collection, intervention/teaching and data analysis); participants; number of participants; education of participants; teaching modality; methodological context (natural or not); training proposal made (individual or group application, presence of people who are part of the natural teaching condition, contents taught). The number of publications for the analyzed period is small and there is dispersion in the publication vehicles, with a tendency of greater frequency in the "RBTCC" and "Psychology of Education" journals. The same tendency to dispersion was found among authors, instruments and materials used for data collection and analysis, as well as teaching procedures used. The works are predominantly empirical/experimental and the most used design is the AB (pre- and post-test or baseline, intervention and post-test). The participants are, for the most part, teachers, and there is also the presence of caregivers with pedagogical function. The number of subjects tends to be less than 10 and there is no defined tendency in their schooling (specially the caregivers). The studies that mention levels of education point to the prevalence of elementary and junior high school, with absence of studies directed to high school and college levels. The type of education most contemplated in the studies that present the information is the regular one, and the type of school, the public one. The most used setting is the school environment. Few works have included the content "basic concepts" in their formative proposals, the opposite occurring with the content "intervention procedures and behavior management". The target behaviors focused present dispersion, and only two works taught curricular adaptation skills. Most of the papers (11) report the total reach of the proposed objectives, but three indicate partial reach, which evidences its effectiveness already proven by the literature in other areas, such as special education and clinics. It is suggested that new studies be carried out to analyze the individual proposals in their organicity, as well as more formative proposals aimed at the school setting and teachers, in order to reach a larger number of people who need effective contributions, based on scientific evidence.